The Distribution of Chlorophyll-aand Its’ Correlation with Related Indicators in the Ulansuhai Lake, China - Wang, Xufeng Mao Changhai; Wei, Xiaoyan; Chen, Qiong (Journal of Environmental Accounting and Management, 2026)
The current study analyzed the spatial and temporal distribution characteristics of chlorophyll-a(Chl-a) based on the bimonthly monitoring data in the Ulansuhai Lake from May to November in 2013. Correlation between chlorophyll-aand related factors including Total Phosphorus(TP), Total Nitrogen(TN), Ammonia Nitrogen(NH4–N), Nitrate Nitrogen (NO2–N), Total Organic Carbon(TOC), Chemical Oxygen Demand (COD) and pH were also analyzed to find the influencing factors of chlorophyll-a. Results indicate that the concentration chlorophyll-awas reduced along with water flowing from North to South. The peak concentration and the foot concentration of chlorophyll-a occurred in July and November, respectively. Except for indicator COD, other factors present a certain correlation with chlorophyll-a. Negative correlation appeared in TOC (R = 0.650, p < 0.05) and pH (R = 0.951, p < 0.01) and positive correlation occurred in TP (R = 0.787, p < 0.01), TN (R = 0.796, p < 0.01), NH4 –N (R = 0.778, p < 0.01) and NO2–N (R = 0.656, p < 0.01). There is no primary factor that dominate the concentration of chlorophyll-a in the water. The current research may provide scientific basis for eutrophication control and management of eutrophic lakes.